The ImpactAssets handbook for investors : generating social and environmental value through capital investing (ANTHEM Press, 2017)
"The ImpactAssets Handbook for Investors offers an introductory overview for investors interested in generating financial returns with the creation of social and environmental impact. In addition to discussions of portfolio structure and strategy, the handbook offers an overview of due diligence necessary to assess potential investments, a discussion of communications and performance measurement issues and other factors key to managing capital for multiple returns. While not an "answer book," The ImpactAssets Handbook for Investors, with contributions from some of the field's leading experts in impact investing, offers practical insights and presents critical questions every investor should consider in creating an investment strategy and executing the deployment of investment capital."--